Local skilled labour shortage in Malaysia construction industry / Nur Farahin Sujarni - Sujarni, Nur Farahin (Faculty of Architecture, Planning and Surveying, 2015)
Over the last decade the construction industry in Malaysia has undergone many changes in order to compete in the age of globalization. High employment demand not only felt by the construction sector, but all sectors of the economy. Although the construction industry is facing the problem of lack of employment from the local, but the problem has been reduced by hiring foreign labour. In addition to lack of local employment, the construction sector is also facing problems related to local skill labour. Therefore, this study aims to look more closely at the problem of a shortage of local skilled labour, especially investigate the factors that may contribute to the shortage of local skilled labour in the Malaysian construction industry and also provide recommendation for increasing participation of local skilled labour in the Malaysian construction industry. The method of the study involved a literature review and also an interview with the respondent which consists of industry key player among Malaysian citizen that has been working in the construction industry involving engineers, contractors, project manager and others. In conclusion, the factors that may contribute to the shortage of local skilled labour are low assuredness of salary, poor career path, poor image of the industry and working environment and education level. On the other hand, the best ways to increase the participation of local skilled labour in the Malaysian construction industry are by commercialized the name of the skill training program, implement specific training, especially for local youth in enhancing their skill levels, the government gives support for smaller companies to train the local workforce, increasing the salary or wages of the local worker and last but not least minimizes the intake of foreign labor in the construction industry.